(untitled) (Journal of Pedagogical Inventions and Practices, 2026)
This article analyzes the pedagogical mechanisms for improving internationalization processes in the higher education system of Uzbekistan. The study highlights the pedagogical significance of academic mobility, international cooperation, digital educational technologies, joint educational programs, and scientific integration. In addition, ongoing reforms in Uzbekistan’s higher education system are examined through the lens of international experience, while existing challenges and possible solutions are identified. The findings demonstrate that pedagogical integration, competency-based education, digital transformation, and scientific cooperation are essential factors for effective internationalization